2019
DOI: 10.4103/ijt.ijt_103_17
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of trichoscopic findings in androgenetic alopecia and the disease severity

Abstract: Background: Androgenetic alopecia (AGA) refers to the appearance of the common nonscarring progressive patterned loss of terminal hair on the frontal scalp and/or vertex of the scalp in both men and women, seen with increasing age in genetically predisposed individuals. Until recently, a scalp biopsy was the only objective tool to diagnose and monitor the disease severity. Trichoscopy of scalp is a new noninvasive technique applied to facilitate the diagnosis of hair and scalp disorders using a ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 18 publications
1
21
2
1
Order By: Relevance
“…Hu et al 9 observed this finding in 24% of FAGA patients. This disparity of findings can be due to different skin phenotypes with variation in sebaceous gland activity as well as degree of pigmentation of scalp as suggested by Ummiti A et al 8 Focal atrichia referred to as pencil erased focal loss of hair was found in 18.6% in our study nearer to that observed by Ummiti A et al 5 (24%) whereas Hu et al 9 & Zhang et al 1 reported its incidence in more than half of their patients. Zhang et al 1 correlated this finding with advancing stage o f androgenic alopecia.…”
Section: Discussioncontrasting
confidence: 45%
See 2 more Smart Citations
“…Hu et al 9 observed this finding in 24% of FAGA patients. This disparity of findings can be due to different skin phenotypes with variation in sebaceous gland activity as well as degree of pigmentation of scalp as suggested by Ummiti A et al 8 Focal atrichia referred to as pencil erased focal loss of hair was found in 18.6% in our study nearer to that observed by Ummiti A et al 5 (24%) whereas Hu et al 9 & Zhang et al 1 reported its incidence in more than half of their patients. Zhang et al 1 correlated this finding with advancing stage o f androgenic alopecia.…”
Section: Discussioncontrasting
confidence: 45%
“…White peripilar sign ( WPPS) was noticed in 44.2% of patients in the present study. Its incidence varied from 15 to 68% in various studies 1,8,9 Yellow dots(YD) were seen in 40 out of 70 pts (57%) in our study. Contrastingly its incidence was high (88%) in Ummiti A et al 8 and very low in Zhang et al 1 study(1.67%).…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Процес мініатюризації волосся при ВВЖТ/АГА може супроводжуватись лімфогістіоцитарною запальною інфільтрацією периінфундибулярної частини фолікула. При гістологічному дослідженні цей феномен описується як мікрозапалення, є специфічним для ВВЖТ/АГА і відрізняє її від рубцевих форм алопеції, за яких має місце більш поширене запалення і склеротичні зміни [26, 48,50].…”
Section: втрата волосся за жіночим типом/ андрогенетична алопеція у чunclassified
“…It can be brown sign, which is seen in early grades of FPHL and white peripilar sign, seen in later grades. [ 30 ] Yellow dots may be seen in more advanced cases, probably as a result of sebum and keratin accumulation in dilated follicles. With increased thinning of the hairs, there is greater penetration of ultraviolet radiation into the scalp and changes typical of photoaging, such as the honeycomb pigmented network, may occur.…”
Section: Introductionmentioning
confidence: 99%